Ardis da sedução e estratégias de liberdade : escravos e senhores nos anúncios de jornais do Espírito Santo (1849-1888) - Ferreira, Heloisa Souza (2012)
This dissertation analyzes the slave advertisements published in four newspapers of the Province of the Espírito Santo in the nineteenth century: Correio da Victoria (1849-1872), Jornal da Vitoria (1864-1869), O Constitucional (1885-1889) and the Espírito Santense (1870-1899). We analyze these documents as discursive constructions of slave identity made according to master s convictions, within a patterns of expectations of what is intended in terms of qualities, virtues and defects of the captives. Although this documentation is characterized by the look of the person making, that is, the owners of slaves, a more detailed analysis allowed us to perceive aspects of their daily struggles, habits, values, ways of dressing, to celebrate and to demand better living conditions. In developing the analysis we perceive that the journals had a fundamental importance to society of the Province of the Espírito Santo of the nineteenth century. These newspapers have a social function that went beyond the issues advocated by partisan political groups and associations that remained: they also functioned as a kind of informal justice, acting as a kind of coercive power, warning violators of the law of the persistence in flogging entail legal disputes, as well as their public exposure. This finding directed us to the hypothesis that by communicating a notice of escape of a slave in the newspapers, the advertiser also sought the return of the captive, report a problem, namely, the flogging of private property by other individuals in the society, that many sometimes the sources were named as seductive. These seductive could be better seen in this study with the help of some investigations found these contentions involving leakage of slaves, which revealed that these harbourer did not have many tricks to entice captives, or, in some cases, they were seduced.